BOOK REVIEW: V. P. Bharatiya, Syed Khalid Rashid's Muslim Law (Eastern Book Company, Lucknow, 2004). Pp. 394. Price: Rs. 195 - Das, Mononita Kundu (NLUJ, 2004)
Islamic law as it exists today is the result of continuous process of development. According to the classical theory, it consists of the express injunctions of the Koran; of the legislation introduced by the 'practice' (sunna) of the Prophet; and the judicial decisions. Landmark decisions bringing about holistic dimension to the Islamic law in the fields relating to divorce, mehar, maintenance, remarriage on motivated conversion, wakf beneficiaries, wakf boards, pre-emption has resulted in the tremendous development of Islamic law.